A Critical Examination of Subgroup Analyses: The National Acute Spinal Cord Injury Studies and Beyond - Hextrum, Shannon; Bennett, Stephanie (Frontiers in Neurology, 2018)
The use of high-dose methylprednisolone for acute spinal cord injury continues to be a topic of debate. This controversy largely stems from fundamental issues in statistical interpretation of trial data, most notably subgroup analyses. The purpose of this review is to discuss important examples of improper subgroup analysis and encourage better practices in future research.